Impact of tRNA-induced proline-to-serine mistranslation on the transcriptome of Drosophila melanogaster. - Isaacson, J.R.; Berg, M.D.; Yeung, W.; Villén, J.; Brandl, C.J.; Moehring, A.J. (G3 : genes - genomes - genetics, 2024)
Mistranslation is the misincorporation of an amino acid into a polypeptide. Mistranslation has diverse effects on multicellular eukaryotes and is implicated in several human diseases. In Drosophila melanogaster, a serine transfer RNA (tRNA) that misincorporates serine at proline codons (P?S) affects male and female flies differently. The mechanisms behind this discrepancy are currently unknown. Here, we compare the transcriptional response of male and female flies to P?S mistranslation to identify genes and cellular processes that underlie sex-specific differences. Both males and females downregulate genes associated with various metabolic processes in response to P?S mistranslation. Males downregulate genes associated with extracellular matrix organization and response to negative stimuli such as wounding, whereas females downregulate aerobic respiration and ATP synthesis genes. Both sexes upregulate genes associated with gametogenesis, but females also upregulate cell cycle and DNA repair genes. These observed differences in the transcriptional response of male and female flies to P?S mistranslation have important implications for the sex-specific impact of mistranslation on disease and tRNA therapeutics.